Causes and outcomes of sepsis in southeast Asia: a multinational multicentre cross-sectional study - Sudarmono, P; Aman, AT; Arif, M; Syarif, AK; Kosasih, H; Karyana, M; Chotpitayasunondh, T; Vandepitte, WP; Boonyasiri, A; Lapphra, K; Chokephaibulkit, K; Rattanaumpawan, P; et al. (Elsevier, 2017)
Background Improved understanding of pathogens that cause sepsis would aid management and antimicrobial selection. In this study, we aimed to identify the causative pathogens of sepsis in southeast Asia. Methods In this multinational multicentre cross-sectional study of community-acquired sepsis and severe sepsis, we prospectively recruited children (age ≥30 days and <18 years) and adults (age ≥18 years) at 13 public hospitals in Indonesia (n=3), Thailand (n=4), and Vietnam (n=6). Hospitalised patients with suspected or documented communityacquired infection, with at least three diagnostic criteria for sepsis according to the Surviving Sepsis Campaign 2012, and within 24 h of admission were enrolled. Blood from every patient, and nasopharyngeal swab, urine, stool, and cerebrospinal fl uid, if indicated, were collected for reference diagnostic tests to identify causative pathogens. We report causative pathogens of sepsis and 28-day mortality. We also estimate mortality associated with enrolment with severe sepsis. This study was registered with ClinicalTrials.gov, number NCT02157259. Findings From Dec 16, 2013, to Dec 14, 2015, 4736 patients were screened and 1578 patients (763 children and 815 adults) were enrolled. Dengue viruses (n=122 [8%]), Leptospira spp (n=95 [6%]), rickettsial pathogens (n=96 [6%]), Escherichia coli (n=76 [5%]), and infl uenza viruses (n=65 [4%]) were commonly identifi ed in both age groups; whereas Plasmodium spp (n=12 [1%]) and Salmonella enterica serovar Typhi (n=3 [0·2%]) were rarely observed. Emerging pathogens identifi ed included hantaviruses (n=28 [2%]), non-typhoidal Salmonella spp (n=21 [1%]), Streptococcus suis (n=18 [1%]), Acinetobacter spp (n=12 [1%]), and Burkholderia pseudomallei (n=5 [<1%]). 28-day mortality occurred in 14 (2%) of 731 children with known statuses and 108 (13%) of 804 adults. Severe sepsis was identifi ed on enrolment in 194 (28%) of 731 children and 546 (68%) of 804 adults, and was associated with increased mortality (adjusted odds ratio 5·3, 95% CI 2·7–10·4; p<0·001). Interpretation Sepsis in southeast Asia is caused by a wide range of known and emerging pathogens, and is associated with substantial mortality.